2011
DOI: 10.1002/elps.201000519
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic fingerprint metallothionein analysis as a potential prostate cancer biomarker

Abstract: Prostate-specific antigen (PSA) is a routinely used marker of prostate cancer; however, the cut-off values for unambiguous positive/negative prostate cancer diagnoses are not defined. Therefore, despite the best effort, certain percentage of misdiagnosed cases is being recorded every year. For this reason, search for more specific diagnostic markers is of great interest. In this study, systematic comparison of PSA and metallothionein (MT) levels in blood serum of 46 prostate cancer-diagnosed patients is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…We subsequently performed correlation analyses between caveolin-1 and other potential serum markers of prostate cancer, which we have determined in our previous studies on the same sample set of patients (59). Thus, regarding PSA, which is mentioned in this table for overall complexity, here we show associations of caveolin-1 with MT and AMACR (Fig.…”
Section: Resultssupporting
confidence: 61%
“…We subsequently performed correlation analyses between caveolin-1 and other potential serum markers of prostate cancer, which we have determined in our previous studies on the same sample set of patients (59). Thus, regarding PSA, which is mentioned in this table for overall complexity, here we show associations of caveolin-1 with MT and AMACR (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Metallothionein has been previously demonstrated by our group as a prostate cancer tumor marker with high sensitivity and specificity [23]. In this study, we demonstrate that alpha-methylacyl-CoA racemase does not differ in serum of prostate cancer patients and controls, however, AMACR is distinctly higher in high-grade (Gleason score 9) tumors and level of MT shows a descending trend in relation to Gleason score.…”
Section: Discussionsupporting
confidence: 50%
“…Metallothionein, AMACR, free PSA and total PSA levels were detected in the blood serum of prostate cancer patients and volunteers to assess their applicability as markers of prostate cancer. Our group has previously shown that serum MT levels are elevated with high level of specificity and sensitivity in prostate cancer patients with possible application as an additional tool for prostate cancer diagnosis [23]. Compared to previous study, in this paper the group of tested samples has been enlarged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation, separation, detection, and/or quantification of MT are not easy tasks for modern bioanalytical chemistry. From the point of view of MT separation, electrophoretic methods have several advantages [11][12][13][14][15][16][17][18][19][20][21][22][23][24].Numerous methods and approaches have been developed to shorten the time of isolation and to obtain biologically important molecules with sufficient purity to be Abbreviations: AO, Acridine orange; MP, paramagnetic or superparamagnetic particle/bead; MT, metallothionein; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide …”
mentioning
confidence: 99%